Planning the Reading Corner Program in Cikeusi Village District. Darmaraja of Sumedang Regency - Firmansyah, Agus; Suherman, Anisah Dayanti; L Gaol, Wita Fricilia; Wahyudin, Uyu (Universitas Pendidikan Indonesia (UPI), 2023)
Reading is a path to success in life because by reading we can access all the knowledge that exists in this world. This activity aims to reactivate the previously activated reading corner, and increase literacy among the community in Cikeusi Village, District. Darmaraja District. Sumedang. In this research, the method used by researchers is descriptive qualitative research. Descriptive qualitative research aims to create a description or painting of the facts and characteristics of a particular population or area in a systematic, factual and thorough manner. Cikeusi Village has a reading corner but it is not utilized optimally. This is due to a lack of enthusiasm from village residents to read the books in the reading corner and also a lack of outreach from the village to village residents so that many village residents still have minimal knowledge, as well as the absence of a system applied to the operation of the reading corner, such as bookkeeping for borrowing books, sloppy organization and unkempt premises. The conclusions stated strengthen the urgency for active involvement of the Cikesi Village community in planning community education programs that have good and optimal results.